Penerapan pupuk hayati dalam meningkatkan produksi jagung (Zea mays L.) di Kabupaten Limapuluh Kota - Yun Sondang; Ramond Siregar; Khazy Anty (Unri Conference Series: Community Engagement, 2019)
The objectives of this activity are to disseminate the results of research to increase corn production in Limapuluh Kota District, to increase knowledge and skills of the community in making and using biofertilizers, and corn cultivation techniques. The method used is "Technology Transfer" with an integrated approach to motivate the community in a sustainable agriculture program with training, mentoring, and demonstration methods in Payakumbuh State Agriculture Polytechnic Experimental Field from August 2018–June 2019. The implementation consists of three stages: Training in house, manufacture of biofertilizers and application of biofertilizers on corn plants. Sources of bacterial inoculants are the Bacillus and Pseudomonas genera which are the result of isolation and identification of three locations of bamboo, corn, and rice plants in Limapuluh Kota District. Bacteria were inoculated when biofertilizers made from water hyacinth and fermented for 6 weeks and applied to a plot of land measuring 250 m2. The results showed the enthusiasm of the community in participating to make biofertilizers and demonstration plots. The output of this activity: Increased corn production 19% than without biofertilizer, increased of knowledge and skills of community in making and applying biofertilizers on plant increased 20–30%.